Exodus : an exegetical commentary - Hamilton, Victor P. (Grand Rapids, Mich. : Baker Academic, 2011)
"Victor Hamilton, a highly regarded Old Testament scholar with over thirty years' experience in the classroom, offers a comprehensive exegesis of the book of Exodus. Written in a clear and accessible style, this major, up-to-date, evangelical, exegetical commentary opens up the riches of the book of Exodus. Hamilton relates Exodus to the rest of Scripture and includes his own translation of the text. This commentary will be valued by professors and students of the Old Testament as well as pastors" -- Publisher description.
Oppression in Egypt (1:1-6:1) -- Liberation from Egypt (6:2-15:21) -- Testing time in the wilderness (15:22-18:27) -- Covenant and law at Sinai (19:1-24:18) -- How to build the tabernacle (25:1-31:18) -- The golden calf and covenant renewal (32:1-34:35) -- Tabernacle built, God's glory fills (35:1-40:38).
Includes bibliographical references and indexes.
Keywords: Bible. -- Commentaries; Kommentar